Hubungan Peran Suami dan Social Culture dalam Pemberian ASI di Pekanbaru, Riau - Siregar, Yossi Yolanda; Lestari, Widia; Hasanah, Oswati (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2022)
Introduction: The low breastfeeding rate for infants is known to be influenced by the role of the husband and the social culture applied to a family. The purpose of this study was to determine the relationship between the role of husbands and social culture with breastfeeding in the Rejosari Health Center Work Area, Pekanbaru City.Methods: The research design is correlational with the research variables of husband's role, social culture, and breastfeeding. The sample in this study was 75 respondents with the criteria that the mother lived with the baby and husband, the mother was willing to be a respondent, the mother was physically and mentally healthy, and the mother was able to read and write using purposive sampling data collection techniques. The analysis in this study is a bivariate analysis using the Chi-square test.Results: As many as 56% of husbands have a low role in supporting breastfeeding and 44% of husbands have a high role in supporting exclusive breastfeeding. Based on social culture, there are 52.8% of mothers who behave positively but give non-exclusive breastfeeding. The results of statistical tests showed a significant relationship between the husband's role and breastfeeding with the results of p value (0.000) < (0.05), while the social culture variable with exclusive breastfeeding showed no significant relationship where the p value (0.183) > (0.05).Conclusion: The high role of husbands in supporting mothers can affect mothers in giving exclusive breastfeeding, while social culture does not have a significant relationship with exclusive breastfeeding.